The mixed blessing of responsibility relief: An application to household recycling and curbside waste collection - Andersson, Sara; Söderholm, Patrik; Berglund, Christer (Frontiers in Environmental Economics, 2023)
This paper addresses the role of personal norms and warm glow in influencing households’ waste recycling preferences. The purpose is to explore inter-household differences in the preferences towards the introduction of curbside recycling, which implies that households are relieved from the responsibility of transporting sorted waste to assigned drop-off stations. One key theoretical point of departure for the analysis is an existing model that integrates norm-motivated behavior into neoclassical utility theory. This builds on the assumption that household members have preferences for upholding a self-image as responsible – norm-compliant – persons, and it also contains a warm-glow component. The empirical investigation relies on a postal survey to households in a Swedish municipality, and this asks households about their willingness-to-pay (WTP) for the introduction of a curbside recycling scheme, as well as about time use and the presence of personal norms and warm glow motives. The results are based on a Heckman selection specification and show that individuals expressing a strong personal norm for recycling are more likely to be willing to pay for curbside recycling, while those with strong warm glow motives are less likely to do so. This suggests the existence of a mixed blessing of responsibility relief. Curbside recycling implies that households are relieved from a moral responsibility that takes time away from leisure activities, but they also experience a loss in warm glow as such a scheme removes the possibility to pursue something that they have learned to appreciate. There could then exist ‘motivational inertia’ making it difficult for policy makers to activate personal norms for new pro-environmental household activities in replacement of existing ones.